Đặc trưng và hoạt tính xúc tác cho phản ứng oxi hóa CO của các oxit CuO, CeO2 và oxit hỗn hợp CuO-CeO2 - Thương Huế, Hoàng Thị; Nhiệm, Đào Ngọc (Vietnam Journal of Chemistry, 2014)
CuO-CeO2 mixed oxide with 7.5 % CuO content prepared by co-precipitation method, has been tested for the oxidation of CO conditions at 30-327 oC. Catalysts have been characterized by means of X-ray diffraction (XRD), H2- temperature-programmed reduction (H2-TPR) and Raman spectroscopy. H2-TPR results indicated that there are three CuO species in the mixed oxide: the Cu2+ mostly exists in the bulk CuO and the left in CuxCe1-xO2-d solid solution and finely dispersed CuO species on the surface of CeO2. The calculating results of the oxygen vacancy concentration in CuO-CeO2 mixed oxide from Gaussian deconvolution of Raman spectra showed that, oxygen vacancy concentration in CuO-CeO2 mixed oxide was 4.5 %. Investigated catalytic possibility of CuO, CeO2 and CuO-CeO2 mixed oxide in transformation of CO. The results showed that, CuO-CeO2 mixed oxide has higher catalytic activity compared CuO and CeO2 oxides. The synergistic interaction between CuO and CeO2 is the main factor responsible for high catalytic activity of CuO-CeO2 mixed oxide. At ambient temperature (30 oC), yield of CO treatment of CuO-CeO2 mixed oxide was relatively high (53.2 %) and the transformation of CO almost finished at the temperature 207 oC (98.4 %). Keywords: CuO-CeO2, CO oxidation, co-precipitation, catalyst